A polycentric network strategy for regional diversification of agriculture: theory and implementation - Jordan, Nicholas R.; Wilson, David Sloan; Noble, Kate; Miller, Keith; Conway, Tara Maireid; Cureton, Colin (Frontiers in Sustainable Food Systems, 2023)
Widespread and substantial diversification of current agroecosystems appears fundamental to meeting many grand challenges in agriculture. Despite urgent calls for diversification on regional scales, particularly in regions dominated by industrialized, low-diversity agriculture, strategies for diversification on such scales are in early stages of development, conceptually and practically. We outline such a strategy, and its implementation by the Forever Green Partnership, a public-private-NGO coalition in support of agricultural diversification in the U.S. Midwest region. Our strategy supports introduction and scaling of multiple novel crops in a region, which requires development of many interdependent supporting elements, including supportive markets, infrastructure, policy, finance, and R&D. The core of our strategy is development of sustainable supply chains (SSCs) for a set of novel crops. We define SSCs as rudimentary systems of these supporting elements for novel crops, linking on-farm crop production to end-use markets while advancing economic, environmental, and social sustainability criteria that are demanded by stakeholders. SSCs provide a scaffold upon which fully-developed support systems for multiple novel crops can be constructed, thus driving regional diversification. SSCs cannot be “built in a day”; rather they must evolve as production of novel crops expands over time and space, and as new challenges and opportunities emerge. Therefore, regional diversification requires a system to sustain this evolutionary process across time and multiple novel crops. We posit that an effective system can be built from two crucial elements: a process of conscious and concerted cultural evolution, and a polycentric network that organizes and supports that process. We outline this system and its conceptual basis, and its implementation by the Forever Green Partnership, and associated challenges and accomplishments. Three years after its inception, the Partnership has attracted substantial resources, developed a polycentric network, and some elements of the cultural-evolution process are in place. However, node development is uneven across the network, hindering its operation. In addition to advancing strategies for regional-scale diversification, the Partnership is seeking to advance conceptual and practical understanding of sustainability transitions in agriculture, and to explore the potential value of conscious cultural evolution in such transitions.